Diffusion-Weighted MR Imaging in Normal Human Brains in Various Age Groups - Helenius, Johanna; Soinne, Lauri; Perkiö, Jussi; Salonen, Oili; Kangasmäki, Aki; Kaste, Markku; Carano, Richard A. D.; Aronen, Hannu J; Tatlisumak, Turgut (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Few studies have concerned the absolute apparent diffusion coefficient (ADC) values in the normal human brain and the effect of aging on diffusion. Therefore, our purpose was to determine whether the average ADC (ADCav) values in the various regions of the brain differ with age, sex, or hemisphere and to establish reference values of the absolute ADCav for further studies.METHODS: Subjects (40 men and 40 women) were chosen from a healthy population; age groups were 20–34, 35–49, and 50–64 years and 65 years or older (n = 20 each). All subjects were examined with MR imaging, including conventional and diffusion-weighted imaging in three orthogonal directions with two b values (0 and 1000 s/mm2) at 1.5 T. Bilateral ADCav values were determined in 36 regions of interest encompassing the entire brain.RESULTS: ADCav values were highest in the cortical gray matter ([0.89 ± 0.04] × 10−3 mm2/s; range, 0.78–1.09 × 10−3), lower in the deep gray matter ([0.75 ± 0.03] × 10−3 mm2/s; range, 0.64–0.83 × 10−3), and lowest in the white matter ([0.70 ± 0.03] × 10−3 mm2/s; range, 0.62–0.79 × 10−3). The ADCav values did not significantly change with aging, except for an increase in the lateral ventricles. No difference was observed between women and men or between the hemispheres.CONCLUSION: The data reported herein are representative, and the ADCav values can be used for reference in future studies and in clinical settings.